Hypertension in women: the role of adolescent childbearing - Biplab K. Datta; Muhammad J. Husain; Deliana Kostova (BMC, 2021)
Abstract Background Adolescent childbearing is associated with various health risks to the mother and child, and potentially with adverse socioeconomic outcomes. However, little is known about the role of adolescent childbearing in maternal health outcomes in adulthood. This study investigates the link between childbirth in adolescence and later-life risk of hypertension among women in India. Methods We obtained nationally representative data on demographic and health outcomes for 442,845 women aged 25 to 49 from the India National Family Health Survey (NFHS) 2015-16. We assessed the difference in hypertension prevalence between women who gave birth in adolescence (age 10 to 19) and those who did not, for the full sample and various sub-samples, using linear probability models with controls for individual characteristics, hypertension risk factors, and geographic fixed effects. Results Nearly 40% of the women in the sample gave birth in adolescence. The adjusted probability of being hypertensive in adulthood was 2.3 percentage points higher for this group compared to women who did not give childbirth in adolescence. This added probability was larger for women who gave birth earlier in adolescence (4.8 percentage points) and for women who gave birth more than once in adolescence (3.4 percentage points). Conclusions Adolescent childbearing was strongly associated with a higher probability of adult female hypertension in India. This finding illustrates the intertemporal relationship between health risk factors during the life cycle, informing the importance of addressing adverse early life events (e.g. child marriage and adolescent childbirth) for hypertension outcomes among women in India.